Assessment of the integration of Three-Way Catalytic converter and Thermoelectric Generator - Xun Liu; Yu-Xuan Li; Yuan-Yi Huang; Chu-Qi Su; Yi-Ping Wang (Energy Reports, 2022)
Thermoelectric Generator (TEG) in automobiles is a promising way to recover the exhaust heat, and can effectively increase energy utilization. The integration of a Three-Way Catalytic converter (TWC) and TEG can improve the performance by using the heat generated during catalytic operation but still has poor compatibility. Therefore, it is essential that how to improve the compatibility between TWC and TEG. This paper proposed a new method of the coupled carrier of the TWC to enhance the catalytic efficiency and increase the output of TEG. The new TEG was tested under steady and transient conditions. The results showed that the temperature uniformity of TEG is improved. The maximum output power of TEG is increased when TWC with the coupled carrier is working stably. The new TEG with coupled TWC carrier has the highest conversion efficiency for CO, NO, and H2gases. Under the steady and transient conditions, reaction energy is transferred to the hot side of TEG and the performance of the one-sixth TEG output power can be increased to 306.2W by using the appropriate coupled carrier. Theoretically, this research provides the basis for further study.